2008
DOI: 10.1016/j.ejheart.2008.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Dyspnoea versus fatigue: Additional prognostic information from symptoms in chronic heart failure?

Abstract: Background: In non-heart failure populations, dyspnoea reported by the patient as the reason for stopping an exercise test is associated with a worse prognosis than fatigue. Patients with chronic heart failure (CHF) have exercise limitation due to breathlessness or fatigue, but it is unclear whether one symptom confers an adverse prognosis over the other. Methods: Consecutive CHF patients underwent exercise testing with metabolic gas exchange. Upon stopping exercise the dominant symptom reported by the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
1
10
1
Order By: Relevance
“…Comparing prognosis using other measurements. Although some investigators have reported that dyspnea rather than fatigue as the symptom terminating exercise indicates a worse prognosis in CHF (28 -30), other reports and this study do not confirm this (31,32). We found by t test that higher body weight, lower New York Heart Association functional classification, and higher left ventricular ejection fraction significantly improved survival (Table 1).…”
Section: Ob In Chfcontrasting
confidence: 69%
“…Comparing prognosis using other measurements. Although some investigators have reported that dyspnea rather than fatigue as the symptom terminating exercise indicates a worse prognosis in CHF (28 -30), other reports and this study do not confirm this (31,32). We found by t test that higher body weight, lower New York Heart Association functional classification, and higher left ventricular ejection fraction significantly improved survival (Table 1).…”
Section: Ob In Chfcontrasting
confidence: 69%
“…DM and hyperglycemia are strongly implicated as a cause for the progression from asymptomatic left ventricular dysfunction to symptomatic HF, increased hospitalizations for HF, and an overall increased mortality risk in patients with chronic HF [78]. Despite all its benefits, metformin is contraindicated in patients with heart failure due to the potential risk of developing lactic acidosis, a rare but potentially fatal metabolic condition resulting from severe tissue hypoperfusion [79].…”
Section: Introductionmentioning
confidence: 99%
“…The percent of HF patients referring dyspnoea as the cause of exercise limitation varies among studies 6, 9, 23. In the present study, we observed that the first cause for self‐ending a maximal effort referred by patients with chronic HF is fatigue (78% of cases), and dyspnoea was reported in 22% of cases.…”
Section: Discussionmentioning
confidence: 99%